2008
DOI: 10.1096/fj.08-110213
|View full text |Cite
|
Sign up to set email alerts
|

utocrine role of endogenous interleukin‐18 on inflammatory cytokine generation by human neutrophils

Abstract: Neutrophils are key players of innate immunity and influence inflammatory and immune reactions through the production of numerous cytokines. Interleukin-18 (IL-18) is known to stimulate several neutrophil responses, and recent evidence suggests that neutrophils might represent a source of IL-18. Here, we show that neutrophils constitutively produce both IL-18 and its antagonist, IL-18BP. Cell activation does not affect IL-18BP release but leads to an increased gene expression and secretion of IL-18, a process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 61 publications
5
59
0
Order By: Relevance
“…In the present study, we observed a decrease in caspase-3 activity in neutrophils after the combined insult of EtOH and burn injury, and normalization of the caspase-3 activity following the administration of anti-IL-18 antibody. IL-18 has been shown to activate the p38 MAPK pathway in neutrophils (24,40). IL-18 activated p38 MAPK in a Ca 2+ -dependent manner that was directly influenced by the IL-18 concentration and the incubation time (40).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, we observed a decrease in caspase-3 activity in neutrophils after the combined insult of EtOH and burn injury, and normalization of the caspase-3 activity following the administration of anti-IL-18 antibody. IL-18 has been shown to activate the p38 MAPK pathway in neutrophils (24,40). IL-18 activated p38 MAPK in a Ca 2+ -dependent manner that was directly influenced by the IL-18 concentration and the incubation time (40).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from activating the p38 MAPK pathway, IL-18 has also been shown to activate the phosphatidylinositol-3 kinase (PI3K)/Akt pathway (24). PI3K is another key signal transducer for neutrophil survival (43,44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also well recognized that T cell-derived IL-2 can activate NK cells, and recent evidence suggests that Ag-specific IL-2 from effector memory T cells can in effect immediately "recall" NK cells which degranulate and secrete IFN-␥ (35,36). Thus, in the presence of IL-2, IL-12, and IL-18, the local inflammatory responses are directed toward strong type I and IFN-␥ responses (1,26,73). Therefore, the strong expression signature of NK cells observed in these conjunctival samples, which reflects those seen after several natural ocular challenge infections or episodes of disease, could be explained by the boosting effect of antigen-specific effector memory T cells.…”
Section: Vol 78 2010mentioning
confidence: 99%
“…During inflammation VEGF serves as chemoattractant for monocytes and macrophages and stimulates angiogenesis [65,66]. Activated PMN are further able to produce S100A9 and IL-18 [67][68][69], what could explain the elevated mRNA expression and higher protein concentration of these factors detected in MC and milk during disease. IL-18 and S100 proteins are known as mediators of the inflammatory neutrophil response in humans [70][71][72].…”
Section: Discussionmentioning
confidence: 99%